(3GdCQV hGdehGQO hGdGfJGL OQGSI JMdjdjI ebGQfI (B/s - (3MSf, eMeO GHQGgjes ((3GdEScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2004)
(3GdCQV GdHfjI hGdJVGQjS,GdefGN hGdCbGdje GdefGNjI hGdfHGJjI ebhe WHjYj ddEfJGL,GdJQHI hHfjJgG hYhGed JchjfgG ebhe WHjYj ddEfJGL,GdHjFI hGdEfSGf ebhe HTQj aj GdGfJGL,feh GdScGf hJfhY GdcKGaI GdScGfjI ebhe HTQj ddEfJGL aj OQGSI GbdjejI ebGQfI GeQjcG GdCfLdhScShfjI,GdehGQO hGdEfJGL Ch Yde GdLZQGajI GdEbJUGOjI,GdfTGW GdGbJUGOj dCeQjcG GdCfLdhScShfjI,GdRQGYI GdYQHjI heXGgQgGs
(3HjHdjhZQGajG U(B.14s
Keywords: (3GdCMhGd GdEbJUGOjIs; (3GdGfJGLs; (3GdLZQGajG GdEbJUGOjI (B- (3GdJLGQI GdOhdjIs; (3GdRQGYIs